Laparoscopic repair of umbilical and paraumbilical hernias: a prospective and interventional study in government hospital - Patel, Kiren B.; Barot, Mithun V. (International Surgery Journal, 2019)
Background: Umbilical and ventral hernia occurs as a result of weakness in musculofascial layer of anterior abdominal wall. The most important causes are congenital, acquired, incisional and traumatic. UH and VH can be repair by open surgical procedure. A successful series of laparoscopic repair of umbilical hernia and VH was done by Le blanc in 1993. The cost can be optimised by selection of mesh and optimal uses of transabdominal suture and various fixation devices. This original article reveals methods, techniques, indication, contraindication, post-op pain, operative time, surgical site infection recurrence and outcome of laparoscopic umbilical hernia and paraumbilical hernia repair. Methods: A total of 21 patients of ventral hernia (umbilical, paraumbilical and incisional), who underwent laparoscopic hernia repair from October 2014 to October 2016, were selected have taken part in study with valid consent, in B.J. Medical College Ahmedabad Gujarat. All patient study regarding operative time, postoperative pain, postoperative hospital stay, surgical site infection like wound infection, seroma, hernia defect size, mean drain removal and recurrence. Results: Out of 21 patients male are 33% and female are 67%. Mean age of patients is 45 yrs with range being 18-65 yrs. 28%, 33.33%, and 38.1% of patient had umbilical, paraumbilical and incisional hernia respectively. Mean size defect was 7.8 cm2. Mean operative time in this study is 98.6 minute. Mean drain removal is 2.80 day. Mean postoperative hospital stay was 3.3 days. 4.7% had wound infection, 9.5% had seroma formation. There is 0% recurrence in present study. Conclusions: The laparoscopic approach appears to be safe, effective and acceptable. It is also effective in those who are obese, with co morbidities (complex) and who have recurrence from prior open repair and having ascites.